Algumas an?lises sobre mecanismos para prover qualidade de servi?o em redes multim?dia - Ruela, Jos? Carlos (2006)
Abstract With the crescent demand for the use of multimedia applications, like voice and video, and mainly in the ones that demand interactive communications, occurring in real time, new parameters (delay, variation of the delay and loss) start to be important for the good operation of these applications. So, it becomes necessary the provision of QoS (Quality of Service) by the network to support these new applications. This dissertation verifies the efficiency of the use of the mechanisms of QoS that were studied here, showing the viability of its use and implementation in a "best effort" network. Inside of this purpose, this work presents the result of several simulations, where it is proven that, with the appropriate utilization of the scheduling mechanisms and congestion control mechanisms, the use of the applications of VoIP (Voice over IP) can be made possible inside of the acceptable limits of delay and loss, even when the voice traffic shares a communication connection with other traffics in situations of intense congestion. Keywords: QoS, quality of service, scheduling mechanisms, congestion control.